Contribution of Islamic Religious Activities to the Social Intelligence of Adolescents with Gadget Addiction in Temanggung - Liberty Sovi Rahma; Baedhowi Baedhowi; Khanafi Khanafi; Farih Muzaky (Yayasan Azhar Amanaa Yogyakarta, 2023)
This study aims to instill the value of social intelligence in teenagers addicted to gadgets and restore social order among adolescents. The influence of globalization has resulted in social inequality, coupled with the Covid-19 pandemic which shocked the world from 2019 to 2021. This research uses a qualitative approach, with the type of field research (field research) in case study groups. The results of the study show that youth activities play a very important role in the internalization of the value of social intelligence in adolescents addicted to gadgets. Karang Taruna activities that play a role include in the religious field, namely involvement in the administration of mosques, yasinan, sholawat tambourines. The social sector is the commemoration of national holidays, village arts, village libraries, and community service. Lastly in the health sector, namely sports and Youth PIK from activities above the value of social intelligence produced including situational awareness, presence, authenticity, clarity, and empathy.